Diversidade em seqüências da região controle do DNA mitocondrial de populações de Astyanax da Bacia do Alto Rio Paraná - Soria, Thatiana Vanessa (2004)
A fish species considered typical of the Upper Paraná River basin is the species Astyanax altiparanae Garutti e Britski, 2000, previously known as Astyanax bimaculatus. In a previous study, molecular markers have demonstrated high genetic similarities among a population introduced in the Iguaçu River and A. altiparane populations from Keller and Pirapó rivers from the Upper Paraná River basin. In the present work, sequences from the mitochondrial DNA control region (D-loop) were used to evaluate the genetic diversity among A. altiparanae populations sampled in several regions of the Upper Paraná River basin and one A. asuncionensis population from the Paraguay River sub-basin, which belongs to the Medium Paraná basin. This work attempts to contribute for a better characterization of A. altiparanae species and to evaluate the possibility that A. asuncionensis was introduced in the Upper Paraná River basin. This species, like A. altiparanae, had already been identified as A. bimaculatus. All specimens from Upper Paraná were identified as A. altiparanae and those ones from Medium Paraná were identified as A. asuncionensis, on basis of morphological traits. Dloop sequences were polymorphic within each species and also between these two highly related Astyanax species. Genetic distances inferred from mitochondrial DNA sequences revealed that the sampled population from the floodplain of Upper Paraná River, as well as the region downstream the floodplain, consisted indeed of two distinct groups of haplotypes, which are existing in sympatry in this region. The less frequent haplotype is highly similar to those of Keller, Pirapó, and Iguaçu rivers, while the other is genetically differentiated by a significant D-loop polymorphism. The aplotype group predominant in the floodplain and in the area closer to Itaipu was typical of this region, and so far it has not been found in other places of the Upper Paraná River, where it has been studied. The genetic diversity revealed in this analysis could represent a high level of intraspecific polymorphism originated from two diverse ancestral populations. Another possible explanation could be the existence of an undiagnosed species in the floodplain of Upper Paraná River. It is conceivable that this hypothetical undiagnosed species could have been introduced in the floodplain, and it could not be discriminated from A. altiparanae on basis of the currently available morphological markers.